Dissemination of Evidence-Based Recommendations for Sickle Cell Disease to Primary Care and Emergency Department Providers in North Carolina: A Cost Benefit Analysis - Paula Tanabe; Audrey L. Blewer; Emily Bonnabeau; Hayden B. Bosworth; Denise H. Clayton; Nancy Crego; Marian F. Earls; Kern Eason; Grayson Forlines; Gary Rains; Matthew Young; Nirmish Shah (Journal of Health Economics and Outcomes Research)
**Background:** Sickle cell disease (SCD) is a genetic condition affecting primarily individuals of African descent, who happen to be disproportionately impacted by poverty and who lack access to health care. Individuals with SCD are at high likelihood of high acute care utilization and chronic pain episodes. The multiple complications seen in SCD contribute to significant morbidity and premature mortality, as well as substantial costs to the healthcare system.